The attitude of nurses towards the care of elderly people - J. N. Gwala; B. M. Zungu; B. B. Ntombela (Curationis, 1995)
The number of nurses entering the nursing profession is decreasing, but demands placed upon the Health Services are increasing primarily due to the increasing number of people in our society. People are living longer and it is apparent that some extra provision must be made to care effectively for the elderly members of our society. Various studies have shown that care of the elderly is an unpopular clinical field for nurses. (Shape, 1986. Notter, 1992. Vickels 1982).